Development and application of an offense severity index in the evaluation of treatment of individuals convicted of sexual crimes - Link, Eva (Psychology, crime & law, 2023)
Dichotomous recidivism criteria are the main measure of success in forensic treatment studies. However, there is wide agreement that binary outcome measures are too undifferentiated, particularly when official reoffending rates are rather low. Considering previous research on offense severity and the Cambridge Crime Harm Index, we addressed this issue by developing a severity index based on sentencing provisions in the German law. Based on a large dataset of males convicted of sexual crimes who had been released from Bavarian prisons between 2004 and 2008, we analyzed the subgroup of n = 48 individuals who recidivated with a sexual offense. About half of the sample had received treatment during imprisonment. Whereas prior analyses did not reveal a significant treatment effect on dichotomous sexual reoffending, the present harm analyses showed a stronger decrease of sex offense severity for treated compared to untreated participants. Despite some limitations of our study, the results indicate that prison-based treatment might decrease the severity of sexual reoffending in males convicted of sexual offenses. From a harm reduction perspective, our findings support the use of severity measures complementary to dichotomous outcome criteria. The applicability of our severity index and implications for future research on prison-based treatment are discussed.